Fluid mechanics : fundamentals and applications - Cengel, Yunus A.; Cimbala, John M. (Cengel series in engineering thermal-fluid science, 2010)
Covers the basic principles and equations of fluid mechanics in the context of numerous and diverse real-world engineering examples. This book helps students develop an understanding of fluid mechanics by emphasizing the physics, using figures, photographs and visual aids to reinforce the physics